Food composition, daily rations, and volumes of consumption for walleye pollock in the Okhotsk Sea in the 2000s - Konstantin M. Gorbatenko; Anastasiya V. Levitskaya (Известия ТИНРО)
Mean daily ration of walleye pollock (various size) in the Okhotsk Sea is estimated as 2.3 % of fish body weight in spring, 5.4 % in summer, 3.4 % in autumn, and 2.2 % in winter. Its total annual consumption is amounted as 98.88 · 106 t on average for the 2000s. Zooplankton dominated in the diet, with its mean annual grazing 80.42 · 106 t, including 41.84 · 106 t of euphausiids (44.1 % of total consumption) and 19.83 · 106 t of copepods (20.9 %), while only 11.29 · 106 t of nekton (11.9 %) was grazed annually by pollock. Pollock grazed annually 16.7 % of the Euphausia stock, 5.0 % of the Copepoda stock, 40.7 % of the Amphipoda stock, and 1.1 % of the Sagitta stock, on average. About a half (50.7 %) of the nekton total consumption in the Okhotsk Sea is provided by pollock.